Modelling and implementation of a photovoltaic system through improved voltage control mechanism - Usmonov, Shukurillo; Iqbal, Atif; Saleem, Adeel; Khosiljonovich, Kholiddinov Ilkhombek; Odiljanovich, Uzbekov Mirsoli; Ugli, Eraliev Khojiakbar Abdinabi; Ugli, Mamadaliev Musulmonkul Imomali (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Renewable energy dependence is increasing daily due to the decaying of conventional energy sources. Another primary reason is the increment of pollution as well as global warming. Various alternate energy sources are being used to replace conventional ones. Among them, the prominent photovoltaic source provides clean and green energy. This research focuses on energy production through the photovoltaic source. The photovoltaic cells combination is used along with the boost converter to get the maximal power output. The maximum power point tracker was designed and implemented to obtain the optimal power from the photovoltaic cells, which do not provide the desired results. Therefore, the voltage control method is an alternative to the maximum power point tracker. Both methodologies compared at different intensities of solar light. The load is attached to the photovoltaic output to test its reliability and smooth performance. The system is designed using MATLAB simulation, and the desired results are obtained.